Band structure of strained Ge 1− x Sn x alloy : a full-zone 30-band k · p model - Song, Zhigang (2020)
We extend the previous 30-band k· p model effectively employed for relaxed Ge1−xSnx alloy to the case of strained Ge1−xSnx alloy. The strain-relevant parameters for the 30-band k· p model are obtained by using linear interpolation between the values of single crystal of Ge and Sn that are from literatures and optimizations. We specially investigate the dependence of bandgap at L-valley and -valley with different Sn composition under uniaxial and biaxial strain along [100], [110] and [111] directions. The good agreement between our theoretical predictions and experimental data validates the effectiveness of our model. Our 30-band k· p model and relevant input parameters successfully applied to relaxed and strained Ge1−xSnx alloy offers a powerful tool for the optimization of sophisticated devices made from such alloy.